Midfoot Beam-Plate Constructs for Charcot Neuroarthropathy: A Cohort Study with Midterm Follow-Up - Patrick C. McGregor MD; Ryan G. Rogero MD; William C. Skinner MD; Clayton C. Bettin MD (Foot & Ankle Orthopaedics)
Category: Midfoot/Forefoot; Diabetes Introduction/Purpose: Charcot neuroarthropathy (CN) is a complex disease process with degeneration of normal foot architecture. The goal of surgical treatment for CN is achieving and maintaining a plantigrade ulcer-free foot. Operative treatment options for CN vary widely including debridement, exostectomy, and complex reconstruction. The technique of intramedullary beaming of the metatarsals with a supplemental medial locking plate (referred to here as a midfoot beam-plate construct [MBPC]) utilizes large diameter intramedullary cannulated screws with a medial locked plate for midfoot stabilization. Outcomes of MBPC patients, both clinical and radiographic, were evaluated to establish the efficacy and longevity of this fixation strategy as it compares to other methods of surgical management of CN. Methods: Forty patients (41 limbs) with midfoot CN treated at our institution by five fellowship-trained foot and ankle surgeons between January 2014 and October 2023 met inclusion criteria and were included in our MBPC cohort. A retrospective chart review was performed to obtain demographic data, previous treatment data, radiographic (Brodsky) classification, time to intervention, number of re-operations, and clinical outcomes after operative management with MBPC. Lateral Meary’s angle was measured for MBPC patients pre-operatively, at first post-operative radiographs, and final radiographs to use as a proxy for surgical correction of midfoot Charcot deformity. Furthermore, post-intervention outcomes (rates of post-operative ulceration, post-operative infection, and amputation) were compared to our previously reported institutional baseline data of 58 CN patients treated from 2005-2014 with limited and reconstructive techniques other than MBPC. Results: The mean age of the MBPC cohort was 57.6 (range, 37-73) years, mean BMI was 38.0, 82.5% (33/40) of patients had diabetes, and 43.9% (18/41) had an ulcer present at time of surgery. Mean clinical follow-up was 28.6 (range, 4-80) months. 94.4% (17/18) of ulcers present at the time of surgery healed after a MBPC construct was utilized. 19/41 (46.3%) patients developed recurrent or new ulcerations. At final follow-up, 28/41 (68.3%) had a plantigrade, shoeable, ulcer-free foot. Only 6/41 (14.6%) patients in our cohort underwent a major amputation, lower than the rates for our historical limited (21.9%) and reconstructive technique (23.1%) cohorts. Pre-operative lateral Meary’s angle averaged -31 degrees, immediate post-operative measured -5.3 degrees (p< 0.001), and final post-operative was -14.4 degrees (p< 0.001). Conclusion: This study provides patient and outcome data for midfoot beam-plate constructs as a treatment for CN in a large cohort with midterm follow-up. Patients undergoing MBPCs had a relatively low rate of major amputation and more than 2/3 achieved a plantigrade, shoeable, ulcer-free foot at final follow-up. We have also shown that active ulceration is not a contraindication to open reconstructive surgery and that a high rate of ulcer healing can be achieved. Furthermore, surgical correction of midfoot deformity as measured by lateral Meary’s angle was improved and sustained at final radiographic follow-up, demonstrating durability of MBPCs for deformity correction.